2020
DOI: 10.1111/apt.15774
|View full text |Cite
|
Sign up to set email alerts
|

Review article: impact of cigarette smoking on intestinal inflammation—direct and indirect mechanisms

Abstract: Background:The inflammatory bowel diseases, Crohn's disease and ulcerative colitis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 274 publications
0
42
0
1
Order By: Relevance
“…A recent systematic review and meta-analysis has identified age, smoking, diabetes, cardiovascular disease, and respiratory diseases as significant risk factors associated with increased mortality rate and greater risk for critical illness from COVID-19 (32). Every single one of these identified risk factors is also associated with permeability of the immune barrier systems (33)(34)(35)(36)(37). Permeability of the immune barriers may be the essential centerpiece risk factor that is associated with COVID-19 severity, and part of this mechanism may also be associated with the combined impact of cross-reactivity of SARS-CoV-2 with immune barrier proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis has identified age, smoking, diabetes, cardiovascular disease, and respiratory diseases as significant risk factors associated with increased mortality rate and greater risk for critical illness from COVID-19 (32). Every single one of these identified risk factors is also associated with permeability of the immune barrier systems (33)(34)(35)(36)(37). Permeability of the immune barriers may be the essential centerpiece risk factor that is associated with COVID-19 severity, and part of this mechanism may also be associated with the combined impact of cross-reactivity of SARS-CoV-2 with immune barrier proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking affects the gut mucosa through negative effects on homeostasis, epigenetic modification and composition of gut microbiota. 23 The epigenetic effects of cigarette smoke on immune and epithelial cells and neurons may contribute to symptoms; however, this effect is most studied in inflammatory bowel disease, 24 and whether the mechanism linking smoking with FD is via increased microscopic inflammation in the duodenum remains to be clarified. Further, smoking is now known to specifically alter the duodenal microbiome and it is feasible this also plays a key role in the pathogenesis of FD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, near our results, Kuntic et al (2020) detected disturbed NO signaling in the endothelium of mice exposed to e-cigarettes and severe oxidative stress in the aorta, lung, and brain of animals after e-cigarette vapor exposure. Moreover, Papoutsopoulou et al (2020) mentioned that the decreased nitric oxide levels could prevent intestinal mucosal injury, helping to restore epithelial continuity, while its high production resulted in deleterious effects via enhancing the adverse effects of other reactive oxygen species (ROS). Moreover, Abdel Mohsen and Ahmed (2019) declared that iNOS is involved in colitis pathogenesis.…”
Section: Discussionmentioning
confidence: 99%